2021
DOI: 10.1098/rsif.2021.0252
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photothermal absorption in iridescent feathers

Abstract: The diverse colours of bird feathers are produced by both pigments and nanostructures, and can have substantial thermal consequences. This is because reflectance, transmittance and absorption of differently coloured tissues affect the heat loads acquired from solar radiation. Using reflectance measurements and heating experiments on sunbird museum specimens, we tested the hypothesis that colour and their colour producing mechanisms affect feather surface heating and the heat transferred to skin level. As predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…It is Previous mechanistic studies have identified various morphological structures as potential thermal radiators, including bare skin patches 12 and external appendages, such as the ears of elephants 9 , the enlarged claws of fiddler crabs 29 and the beaks of birds 10,11,30 . In addition, secondary sexual signaling characters involving melanin or structural iridescent colors can also have cascading effects on body temperature, and be either beneficial in cold environments or to decrease risk of overheating in hot environments [31][32][33] . While these previous mechanistic studies have provided compelling evidence for the thermoregulatory consequences of various morphological traits, they have not provided direct evidence for their fitness consequences, plasticity, and underlying genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…It is Previous mechanistic studies have identified various morphological structures as potential thermal radiators, including bare skin patches 12 and external appendages, such as the ears of elephants 9 , the enlarged claws of fiddler crabs 29 and the beaks of birds 10,11,30 . In addition, secondary sexual signaling characters involving melanin or structural iridescent colors can also have cascading effects on body temperature, and be either beneficial in cold environments or to decrease risk of overheating in hot environments [31][32][33] . While these previous mechanistic studies have provided compelling evidence for the thermoregulatory consequences of various morphological traits, they have not provided direct evidence for their fitness consequences, plasticity, and underlying genetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Coloration also affects the thermal properties of plumage. Variation in reflectance and absorption of light affect the heating of the feather surface (Wolf & Walsberg 2000, Rogalla et al 2021a. When the plumage surface is heated by the sun under cold conditions, the temperature gradient between the skin and the feathers is reduced, which in return decreases heat loss to the environment (Fig.…”
Section: Functions Of Avian Plumagementioning
confidence: 99%
“…3). Concurrently, melanin-based colours reflect less light than carotenoid-based colours (Rogalla et al 2021a).…”
Section: Determinants Of Plumage Coloration and Their Thermal Propertiesmentioning
confidence: 99%
See 2 more Smart Citations